NEW RELIGIOUS MOVEMENT: MELACAK SPRITUALITAS GERAKAN ZAMAN BARU DI INDONESIA - Retno Sirnopati (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
The growth of new religious movements in various parts of the world, although not labeled as formal religion, is a socio-psychological symptom of loneliness and alienation. This study aims to understand how the influence of the new religious movement on the socio-culture of Indonesian society. The object of this research is every phenomenon of a new religious spiritual movement that has become a separate phenomenon in Indonesian society, especially in decades by identifying the various characteristics contained in it based on the perspective of the social analysis approach of Religion. This research is a qualitative study using a sociological and anthropological analysis approach. The results of this study indicate that the NRM movement emerged as a result of various factors in a society that is changing rapidly, hence efforts to overcome and resolve problems concerning various human lives, whether social, economic, political, educational, psychological, and so on. However, because the emergence of the NRM movement is a religious symptom, one way to overcome it is to seek healthier forms of upholding and living religious values, at least not causing a bad impact on society.